Vitrectomy for diabetic retinopathy: A review of indications, techniques, outcomes, and complications - Nimesh C. Patel; Yi-Ting Hsieh; Chung-May Yang; Maria H. Berrocal; Felipe Dhawahir-Scala; Paisan Ruamviboonsuk; Rajeev Reddy Pappuru; Vivek Pravin Dave (Taiwan Journal of Ophthalmology)
Diabetic retinopathy is one of the most severe forms of retinopathy and a leading cause of blindness all over the world. Of a greater concern is proliferative diabetic retinopathy which leads to vitreous haemorrhage and tractional retinal detachment in such cases. A majority of these cases require a surgical intervention to improve vision and prevent further vision loss. Surgical manouevers in these cases require a complex combination of vitrectomy, membrane dissection, judious usage of endodiathermy, endolaser, vital dyes, bimanual dissection and usage of intraoperative and post-operative tamponades. Each case presents a unique challenge and necessitates an appropriate combination of the steps mentioned above. In the current review we present the current understanding of the need for surgery in diabetic retinopathy, various surgical approaches and a summary of current literature on the same. Multiple surgical video clips demonstrating these steps are also included in this review.